Influence of Sowing Date and Humic Acid Application on Foeniculum vulgare Mill. Growth, Yield, and Essential Oil Composition - Ahmed Samy; Said S. Soliman; Sayed S. A. Abdel-Rahman; Wagdi S. Soliman; Ahmed M. Abbas (Horticulturae)
This study investigated the impact of varying sowing dates and concentrations of humic acid (HA) on the growth, yield, and essential oil profile of fennel (Foeniculum vulgare) across two consecutive growing seasons (2020/2021 and 2021/2022). The experiment was carried out at Aswan University’s Agricultural Experimental Farm in Egypt, utilizing a split-plot design with three sowing dates (15th October, 1st November, and 15th November) along with four HA concentrations (0, 2.5, 3.75, and 5 kg ha−1). The results revealed that early sowing on 15th October and enrichment with 5 kg ha−1 of HA significantly enhanced plant height, stem diameter, branch number, umbels per plant, and fruit yield. The highest fruit yield (2684 kg ha−1) and essential oil yield (27.3 L ha−1) were obtained from plants sown on 15th October and treated with 5 kg ha−1 HA. Moreover, the essential oil composition was notably affected, with significant increases in the concentration of anethole, estragole, and other critical compounds under the same treatment. Conversely, delayed sowing reduced both the yield and oil content. These findings highlight the importance of optimizing sowing dates and HA application rates to maximize fennel’s yield and essential oil quality, particularly in arid regions. The findings of this study offer practical guidance for optimizing fennel cultivation in arid regions by integrating early sowing dates and humic acid applications, which can significantly enhance yield and essential oil quality. These insights are particularly valuable for the medicinal and aromatic plant industries, supporting sustainable agriculture and improving the commercial viability of fennel production under climate-challenged conditions.